Alternate bearing of 'Golden Reinders' and 'Summered' apples - Racskó, J.; Nagy, J.; Szabó, Z.; Soltész, M.; Holb, I. J.; Nyéki, J. (International Journal of Horticultural Science, 2006)
The aim of the present study was to study the effect of biennial bearing (irregular yields) on the generative production of apple cultivars 'Golden Reinders' and 'Summerred' on M.9 rootstock. The observations were made at Nagykutas in West-Hungary for four years. The authors have studied the flowering time, flower density, fruit density, fruit drop, seed content, yielding and fruit quality in the on-year and off-year. Based on the results, it can be stated that the alternation does not cause a significant change in the flowering time of cvs. 'Golden Reinders' and `Summerred': the difference between the flowering time of trees in the on-year and off-year period was 0-1 day. However, there were significant differences in the flower density. 'Golden Reinders' proved to have a weaker tendency to alternation similarly to the statements of the literature. Alternation (off-year) was observed only in three years from the studied four years. While in the case of `Summerred', strong alternation was observed in all four years. In fruit density, there were differences among the cultivars and among the different cycles of biennial bearing. Fruit density (and its opposite, fruit drop) changed inconsistently in the period between flowering and harvest. In the case of 'Golden Reinders' and 'Summerred' 2 and 4 fruit drop periods were detected, respectively. In the off-year, the different periods were less distinct, in most cases they were overlapping each other. The dynamics of fruit drop was related to seed content per fruit. The lower the seed number was, the higher the degree of fruit drop was. In both the high- and off-year cycles, the number of seeds in fruits on the tree and on the ground increased with time. In the yield parameters (fruit number, fruit load, yield efficiency), the differences were greater among the yields of trees in the high- and off-year cycles for 'Summerred'. The fruit quality parameters were greatly influenced by the fruit load of the trees in the different alternation cycles. In general, it can be stated that fruit mass, diameter and height were lower on trees in the on-year. A similar trend could be observed in flesh firmness, cover colour and dry matter content, but the differences were smaller. 'Summerred' was more sensitive to the differences in fruit load.